A game-theoretic analysis on the use of indirect speech acts. Issue 2 (3rd July 2018) - Zhao, M.
Abstract: In this paper, I will discuss why in some circumstances people express their intentions indirectly: the use of Indirect Speech Acts (ISAs). Based on Parikh's games of partial information and Franke's IBR model, I develop game-theoretic models of ISAs, which are divided into two categories, namely non-conventional ISAs and conventional ISAs. I assume that non-conventional ISAs involve two types of communication situations: communication under certain cooperation and that under uncertain cooperation. I will analyse the cases of ironical request and implicit bribery as typical instances of non-conventional ISAs of each situation type, respectively. I then apply the models to analyse the use of conventional ISAs from an evolutionary perspective, which is inspired by Lewisian convention theory. The models yield the following predictions: the use of non-conventional ISAs under certain cooperation relies on the sympathy between interlocutors, which blocks their evolution towards conventional ISAs; in uncertain cooperative situations, people are more likely to use ISAs, which helps their conventionalisation.